Business Development in Emerging Economies on the Basis of Limits and Conditions of National Strategies. (January 2019) - Ulanov, Vladimir Leonidovich
Is it possible for Russian energy companies to develop an effective business strategy based on the restrictions and rules of strategic documents of national scale? Today, Russian Energy Strategy sets the benchmarks for business. World experience confirms the possibility of adjusting corporate strategies for the benefit of society. Danish Energy Strategy prescribes a smooth transition to alternative energy sources and active implementation of smart energy resources. Experience of Norway in this area is also important. The third energy package of the EU defines the rules of the game, influencing business models, strategies and long-term deliveries of external counterparties. The set of methods allows for the analysis of open sources and materials for the development of national and corporate strategies. Management technologies allow us to specify and quantify the characteristics of the national energy strategy and to reflect on the priorities in the development strategies of companies. The conditions of the state policy and the parameters of the companies' strategies will have more points of contact and reduce the risk of deviation from the declared goals. Revision of the program document is possible due to organizational design and methodological support.